2018
DOI: 10.1108/pijpsm-11-2016-0160
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of neighborhood context on residents’ satisfaction with police services in metropolitan Taipei

Abstract: Purpose The purpose of this paper is to add to the literature on Taiwanese policing in three regards: employing multiple measures of satisfaction with police services; including analysis of the effects of differing neighborhood contexts; and examining both individual and district-level measures simultaneously to deepen our understanding of influences on citizen satisfaction with police services. Design/methodology/approach Data for the study were obtained from a random-stratified sampling telephone survey of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 21 publications
2
33
0
3
Order By: Relevance
“…The local crime environment can play an important role in shaping the attitudes of residents toward the police (De Angelis and Wolf, 2016). This claim is supported by many studies showing that crime rates are negatively associated with satisfaction with the police (Kelly and Swindell, 2002; Lai and Zhao, 2018; Reisig and Parks, 2000; Wu et al , 2009). In terms of disorder, a number of studies have shown that satisfaction with police was significantly lower in disordered areas (Dai and Jiang, 2016; Lai and Zhao, 2018; Reisig and Parks, 2000; Sprott and Doob, 2009).…”
Section: Literature Reviewmentioning
confidence: 70%
See 3 more Smart Citations
“…The local crime environment can play an important role in shaping the attitudes of residents toward the police (De Angelis and Wolf, 2016). This claim is supported by many studies showing that crime rates are negatively associated with satisfaction with the police (Kelly and Swindell, 2002; Lai and Zhao, 2018; Reisig and Parks, 2000; Wu et al , 2009). In terms of disorder, a number of studies have shown that satisfaction with police was significantly lower in disordered areas (Dai and Jiang, 2016; Lai and Zhao, 2018; Reisig and Parks, 2000; Sprott and Doob, 2009).…”
Section: Literature Reviewmentioning
confidence: 70%
“…This claim is supported by many studies showing that crime rates are negatively associated with satisfaction with the police (Kelly and Swindell, 2002; Lai and Zhao, 2018; Reisig and Parks, 2000; Wu et al , 2009). In terms of disorder, a number of studies have shown that satisfaction with police was significantly lower in disordered areas (Dai and Jiang, 2016; Lai and Zhao, 2018; Reisig and Parks, 2000; Sprott and Doob, 2009). In sum, residents feel that the police are responsible for the safety and quality of life in the community (Reisig and Parks, 2000), and satisfaction with the police may decrease if the police are unsuccessful in controlling crime and disorder (Bridenball and Jesilow, 2005).…”
Section: Literature Reviewmentioning
confidence: 70%
See 2 more Smart Citations
“…Trust was included as an independent variable in these studies, suggesting that trust in police leads to higher levels of collective efficacy. Studies that included trust as a dependent variable also tended to find positive associations between collective efficacy/informal social control and trust (Bradford et al, 2009;Jackson et al, 2013;Kirk and Papachristos, 2011;Kwak and McNeeley, 2019;Lai, 2016;Lai and Zhao, 2018;Maxson et al, 2003;Rodrigues, 2010), suggesting that the relationship between these variables may be bi-directional (although the cross-sectional nature of the data makes it impossible to be sure).…”
Section: Relationship Between Policing and Collective Efficacymentioning
confidence: 99%